Separação adsortiva de misturas etanol-água por processo PSA - Moreira, Alexandre Marques (Universidade Federal de São Carlos, 2005)
The ethanol is one of the most well-known and diffused fuels sources in nowadays, therefore the domain of its technology has a great importance to the producer countries. Beyond it is in general, lesser expensive than the major part of the petrochemical fuels, the ethanol has its origin in the renewable sources that becomes Brazil in a world power on its production. From these facts the present work consists on the application of the PSA (Pressuring Swing Adsorption) process on the ethanol purification, from ethanol-water mixtures with compositions that simulate ethanol concentrations of the final steps of distillation process. To get this ethanol purification it was used the zeolite 3A as adsorbent, which adsorbed the water of the mixtures in a pressured bed. The PSA process were composed by four steps: The first was the adsorption bed pressurization, at high temperature, with a given ethanol-water mixture; the second was the residence of the fed mixture for a given time in the bed to recover the ethanol; the third was the depressurisation of the bed to the ambient pressure, and the fourth was the regeneration of the adsorbent by vacuum, to recover the water adsorbed. The process variables studied in this work were adsorption pressure, adsorption time and initial concentration, being evaluated their influences on the response variables fluid phase enrichment, ethanol recover and process productivity, were studied, through a factorial planning. These influences were described by polynomial models, in which were applied the statistical tests F and R2, to analyse the quality of the obtained adjustments. The obtained models were validated by extra experiments done out of the factorial planning. The influences of the process variables over the response variables were analysed through response surfaces generated by the obtained polynomial models. The response variables were individually optimized with the using of search programs, which sought the best results over the polynomial models and the process variable ranges. The individual optimum results of the response variables were found, at the same way, the values of the process variables that produced these results. The response variables were also optimized together simultaneously. To obtain these optimizations search programs, with the same logic of the used in the individual optimization, were used with the multiresponse method, which made possible the obtainment of the optimum values of response variable arrangements in pairs and all of these together simultaneously. These optimum values to these arrangements were obtained, at the same way that the process variable values, which correspond to these optimizations. The enrichment obtained results showed high values and low variations with the increase of the adsorption time. At the same way, the adsorption pressure influences the enrichment significantly only with low values of the initial concentration and adsorption time. The enrichment had also an increase of its value and a decrease of its variation, with the increase of the initial ethanol concentration. The ethanol recover showed without significantly influence with the variations of the adsorption time and the adsorption pressure, however had an increase with the increase of the initial concentration. The productivity profiles showed that they were influenced by the three process variables. The increase of the productivity was detected with the increase of the initial concentration and the increase of the adsorption pressure. The productivity decreased with the increase of the adsorption pressure. The obtained results to the simultaneous optimizations showed that the productivity had a predominant influence over the other response variables optimized with these. At the same way, the recover values were not influenced by the optimization of the others response variables. Also it was seen that the enrichment optimization impaired the productivity results, in spite of the reverse fact had not been verified. To illustrate the generated results of the optimizations, the next values were obtained to the optimization of the three response variables simultaneously: 94.7% to the fluid phase enrichment, 82.5% to the ethanol recover and 5.14g.g-1.h-1 to the process productivity, with the values of the process variables of 10 bar to the adsorption pressure, 90% to the initial ethanol concentration and 2.0 minutes to the adsorption time.
Keywords: Adsorção; PSA; Etanol; Zeólita 3A; ENGENHARIAS::ENGENHARIA QUIMICA